(untitled) (Itinera, 2016)
This article examines Adorno’s non-identity thinking and the moral role of mimesis. On the one hand, Adorno criticises Kant’s moral theory, revealing the heteronomy of morality and the untruth of subjective freedom, on the other he defends the utopistic urge of the “transcendental”, moving from finitude and imperfection. Adorno opposes to the bourgeois personality neither a naïve return to nature, nor a getting rid of the subject, but the individual as differentiated coexistence of self and otherness, spirit and nature.